The Effect of Compost Raw Materials (Market Waste, Yard Waste, and Cow Rumen) to Quality and Quantity of Compost - Yommi Dewilda; Rizki Aziz; Hasnureta Hasnureta (Research Centre of Inorganic Materials and Complexs, 2019)
This study combines market waste (MW), yard waste (YW) and cow rumen (CR) as raw materials to obtain the optimum C/N ratio of compost raw materials. Composter consists of 6 variations, namely variation 1 (70% MW: 30% YW), variation 2 (60% MW: 20% YW: 20% CR), variation 3 (50% MW: 30% YW: 20% CR), variation 4 (40% MW: 40% YW: 20% CR), variation 5 (30% MW: 50% YW: 20% CR) and variation 6 (20% MW: 60% YW: 20% CR). This study aims to analyze the effect of variations in compost raw material composition so that the most optimum variation is obtained for the composting process. The method used was semi-aerobic composting. The results of observations on compost maturity for temperature, pH, texture, color and odor parameters have met SNI 19-7030-2004 standards with composting time of 12-21 days. The results of compost quality analysis including water content, organic C, nitrogen, C/N ratio, phosphorus, and potassium have not all variations fulfilled the SNI 19-7030-2004 standard, namely the value of the C/N ratio in variation 6 which exceeds the standard. Of the total compost as much as 3 liters, the solid compost yields of 0.5-1.25 liters and liquid compost from 0.05 to 1.5 liters were obtained. Based on the results of scoring on maturity, quality, and compost quantity, the best variation was found in variation 2